Audit of Management of Gestational Proteinuria [25L]. (May 2017) - Sood, Akanksha; Mathen, Stephy
Abstract : INTRODUCTION: Studies have demonstrated that around 50% of women with isolated proteinuria in pregnancy develop preeclampsia and importantly, even in the absence of hypertension, these women are at significantly increased risk of fetal growth restriction and placental abruption. METHODS: Retrospective audit of cases of Isolated gestational proteinuria. A total of 50 patients were identified who had their urine protein creatinine ratio (uPCR) sent in the January to December 2015. Only cases with isolated gestational proteinuria were identified. RESULTS: Our results showed that 58% of women developed preeclampsia with an average interval of 11 days from first admission with isolated proteinuria. Further, 12% of babies were small for gestational age and 16% delivered less than 37 weeks. A urine culture sensitivity was performed in 76 % women with any degree of proteinuria to exclude urinary tract infection. A urine protein creatinine ratio (uPCR) was requested in 96% when greater than or equal to"+" on urine dipstick. Baseline bloods were done in 98% when urine protein creatinine ratio (uPCR) was greater than 30 mg/mmol or "++" proteinuria dipstick. Only 56% had a management care plan documented by a senior obstetrician. In women with significant proteinuria (even in the absence of hypertension) delivery was discussed and offered after 37 weeks in 86.36%. CONCLUSION: There was marked inconsistency in the management of gestational proteinuria. Universal guideline pathway should be made to avoid adverse outcomes like preeclampsia which is increased in this group.